Naturally Acquired Human Antibodies Against Reticulocyte-Binding Domains of Plasmodium vivax Proteins, PvRBP2c and PvRBP1a, Exhibit Binding-Inhibitory Activity. (3rd April 2017) - Gupta, Enna Dogra; Anand, Gaurav; Singh, Hina; Chaddha, Kritika; Bharti, Praveen K.; Singh, Neeru; Sharma, Yagya Dutta; Gaur, Deepak
Abstract: Background: Crucial gaps in our understanding of Plasmodium vivax reticulocyte invasion and protective immunity have hampered development of vivax vaccines. P. vivax exclusively invades reticulocytes that is mediated by the P. vivax reticulocyte-binding proteins (PvRBPs) specifically PvRBP2c and PvRBP1a. Vivax infections in Duffy-null individuals have suggested the evolution of alternate invasion pathways that may be mediated by the PvRBPs. Thus, PvRBPs appear as potential targets for efficacious P. vivax neutralization. However, there are limited data validating their vaccine efficacy. In the absence of vivax invasion assays, binding-inhibitory activity of antibodies has been reported to be associated with protection and a measure of vaccine potential. Methods: –based analysis was performed of the PvRBP reticulocyte-binding properties and binding-inhibitory activity of specific anti-PvRBP2c/PvRBP1a human antibodies. Results: PvRBP2c and PvRBP1a displayed a distinct reticulocyte-binding specificity, and their specific reticulocyte-binding domains were mapped within their N-terminal regions. Importantly, naturally acquired antibodies against the reticulocyte-binding domains efficaciously blocked reticulocyte binding of native PvRBPs, suggesting that the human immune system produced functional binding-inhibitory antibodies through exposure to vivax malaria. Conclusions: Reticulocyte-binding domains of PvRBP2c/PvRBP1a are targets of naturally acquired binding-inhibitory antibodies, substantiating their promise as candidate antigens against which vaccine-inducible immunity could potentially be boosted through natural infections. Summary: The reticulocyte-specific binding domains of Plasmodium vivax proteins, PvRBP2c and PvRBP1a are targets of naturally acquired binding-inhibitory human antibodies, thus substantiating their promise as candidate antigens for the development of novel P. vivax malaria vaccines.